2015
DOI: 10.4103/0975-7406.168034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of detoxification (tadbeer) in content of toxic metabolites of Strychnos nux-vomica: A Unani approach for its use in human

Abstract: Background:Azaraqi (Strychnos nux-vomica, Loganiaceae) has been the important Unani medicine since long time as a stimulant, anti-inflammatory, and blood purifier. It has been used very frequently by the Unani practitioner. But the Unani system recommends application of azaraqi in medicine only after its detoxification (tadbeer) may be because of the presence of its deadly poisonous alkaloids (strychnine and brucine). In the present investigation, an attempt has been made to quantify the actual content of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Some previous studies have supported the scientific validation of the concept of detoxification/ rectification of herbal drugs. A study has reported that the concentration of toxic constituents such as strychnine and brucine in Strychnos nux-vomica was found to be reduced in the detoxified sample of the test drug 28 . Another study demonstrated that the amount of strychnine was found to be less in the detoxified sample of Strychnos nux-vomica using water and milk 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have supported the scientific validation of the concept of detoxification/ rectification of herbal drugs. A study has reported that the concentration of toxic constituents such as strychnine and brucine in Strychnos nux-vomica was found to be reduced in the detoxified sample of the test drug 28 . Another study demonstrated that the amount of strychnine was found to be less in the detoxified sample of Strychnos nux-vomica using water and milk 29 .…”
Section: Discussionmentioning
confidence: 99%